Power- and Area-Optimized High-Level Synthesis Implementation of a Digital Down Converter for Software-Defined Radio Applications - Sikka, Prateek; Asati, Abhijit R.; Shekhar, Chandra (Circuits, systems, and signal processing, 2021)
In digital signal processing, digital down converters (DDCs) convert digitized, band-limited signals to lower frequency signals at a smaller sampling rate to simplify subsequent filtering stages. Software-defined radio (SDR) is a radio communication system in which components that are traditionally implemented in hardware are implemented in software on an embedded system. DDCs are widely used in modern communication systems, such as SDRs. Herein, we propose a low-power- and area-optimized implementation of a DDC for SDR applications. The DDC was designed using an innovative and novel high-level synthesis (HLS) design method based on application-specific bit widths for data nodes. The results achieved after a field programmable gate array (FPGA) implementation are superior to those obtained from hand-coded register transfer level (RTL) implementations in terms of area and power efficiency, with almost the same speed of operation. Our results were obtained using the MATLAB hardware description language (HDL) coder for HLS and Xilinx Vivado (a software for the synthesis and analysis of HDL designs) for synthesis. The DDC down-converts an input of 200 MHz signal to an output of 2 MHz signal. This implementation was conducted on a real FPGA hardware (Xilinx Kintex-7) and verified against the design specifications using an FPGA in the loop feature of HDL Verifier and MATLAB. In addition, we propose a generic methodology for improving the area, speed, and power for different application designs and HLS tools. The proposed methodology is also applicable to hand-coded RTL designs for any application.